2015
DOI: 10.1186/s40364-015-0046-z
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic models for alcoholic hepatitis

Abstract: Alcoholic hepatitis (AH) is caused by acute inflammation of the liver in patients that consume excessive amounts of alcohol, usually in a background of cirrhosis. AH can range from mild to severe, life threatening disease with a high rate of short and long-term mortality. Prognostic models have been used to estimate mortality in order to identify those that may benefit from corticosteroids or pentoxifylline. This review focuses on the different prognostic models proposed. While limitations of the prognostic mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 53 publications
0
28
0
Order By: Relevance
“…Louvet et al, had observed marked decrease in 6 months survival in the patients having Lille score ≥ 0.45. Mortality was 25 ± 3.8 % in the subgroup of patients having Lille score < 0.45 versus 85 ± 2.5% in the subgroup with Lille score ≥ 0.45 (P value < 0.0001) 14 . We found that there were 68.4% death in subgroup of patients with Lille score ≥ 0.45 whereas there were no death at all in the subgroup with Lille score < 0.45.…”
Section: Fig 2: Percentage Of Deaths In the Two Subgroups Of Lille Smentioning
confidence: 86%
See 1 more Smart Citation
“…Louvet et al, had observed marked decrease in 6 months survival in the patients having Lille score ≥ 0.45. Mortality was 25 ± 3.8 % in the subgroup of patients having Lille score < 0.45 versus 85 ± 2.5% in the subgroup with Lille score ≥ 0.45 (P value < 0.0001) 14 . We found that there were 68.4% death in subgroup of patients with Lille score ≥ 0.45 whereas there were no death at all in the subgroup with Lille score < 0.45.…”
Section: Fig 2: Percentage Of Deaths In the Two Subgroups Of Lille Smentioning
confidence: 86%
“…It is highly predictive of death at six months in patients with alcoholic hepatitis 14 . Lille score may be as accurate at day 4 as at day 7 in predicting response to corticosteroids as well as 90 day mortality 15 .…”
mentioning
confidence: 96%
“…Available scoring systems for assessing the severity and prognosis of AH are Modified MDF based on PT and serum bilirubin concentration; GAHS that uses variables including age, blood urea, peripheral blood leukocyte count, serum bilirubin, and PT; the MELD score using bilirubin, creatinine, and INR levels; the Lille model which combines six variables (age, renal insufficiency, albumin, PT, bilirubin, and evolution of bilirubin on day 7). Scoring systems include differing cut-offs, various clinical and laboratory parameters; combining more than one scoring system, as well as establishing new scoring models, could improve the current practice [8]. CH is symptomatic, biochemical, or serological evidence of continuing or relapsing hepatic disease for more than six months.…”
Section: Discussionmentioning
confidence: 99%
“…The NAFLD Activity Score is used for the assessment of any degree of the NAFLD and is under critical evaluation in many recent studies [7]. Maddrey Discriminant Function (MDF) and Glasgow Alcoholic Hepatitis Score (GAHS) are used for defining severity and predicting mortality in patients with alcoholic hepatitis (AH) [8]. International Autoimmune Hepatitis Group developed a scoring system for diagnostic, differential diagnostic, and prognostic purposes in patients with autoimmune hepatitis (AIH).…”
Section: Introductionmentioning
confidence: 99%
“…The MELD score performs relatively well but its sensitivity and specificity varies depending upon the threshold taken to identify severe disease. This varies between 18 and 25 with no consensus between guidelines or reviews . It should also be noted that the MELD, mDF, ABIC and GAHS are all subject to significant inter‐laboratory variation.…”
Section: Prognostic Scoresmentioning
confidence: 99%